(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Due to the wide range of social experience, the communication processes are changing, and the pragmatic structure, which was originally structured in a natural way, is changing and becoming more complex. This, in turn, leads to the continuous expansion of the semantic shell of pragmatics. Therefore, it is necessary to start linguistic analysis from pragmatics.